2020
DOI: 10.1161/hypertensionaha.119.13239
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and Multidisciplinary Evaluation of Fibromuscular Dysplasia Patients Reveals High Prevalence of Previously Undetected Fibromuscular Dysplasia Lesions and Affects Clinical Decisions

Abstract: Fibromuscular dysplasia (FMD), regarded as a generalized vascular disease, may affect all vascular beds and may result in arterial stenosis, occlusion, aneurysm, or dissection. It has been proposed to systematically evaluate all vascular beds in patients with FMD, regardless of initial FMD involvement. However, the impact of this approach on clinical decisions and on management is unknown. Within the prospective ARCADIA-POL study (Assessment of Renal and Cervical Artery Dysplasia–Poland), we evaluated 232 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
1
26
1
1
Order By: Relevance
“…Haussen et al reported the recurrence rate of 29% in patients treated with pharmacotherapy, whereas no recurrent stroke/TIA was observed in stented patients [ 22 ]. If CaW is found, looking for FMD in other locations should be considered [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haussen et al reported the recurrence rate of 29% in patients treated with pharmacotherapy, whereas no recurrent stroke/TIA was observed in stented patients [ 22 ]. If CaW is found, looking for FMD in other locations should be considered [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…FMD may also be more frequent in SCAD patients with a higher coronary tortuosity score [65]. In the ARCADIA-POL study, including 232 patients with FMD, systematic evaluation including "head-to-pelvis" computed tomography angiography resulted in detection of new FMD lesions in 34.1% of patients and previously undiagnosed vascular complications in 25% of subjects [73]. These findings require confirmation in SCAD-cohort observational studies.…”
Section: Screening For Fibromuscular Dysplasia (Fmd) and Extracoronary Vascular Abnormalities (Eva)mentioning
confidence: 98%
“…Cervical (carotid or vertebral) artery dissection is a frequent event of FMD (Figure 2D). The prevalence varies between 9% and 39.5%, and is highest among patients with a neurological presentation leading to diagnosis of FMD [6,10,11,16,53,59,60]. In the US FMD registry, the prevalence of carotid artery dissection is 3 to 4 times higher than vertebral artery dissection [6,10].…”
Section: Cerebrovascular Fmdmentioning
confidence: 99%
“…The prevalence of FMD in the general population is unknown because this disease is often clinically silent. FMD may be diagnosed during work-up of clinical symptoms and/or signs, but can also be discovered incidentally during imaging tests performed for other reasons [3,16].…”
Section: Introductionmentioning
confidence: 99%